Therapeutics Development for Alagille Syndrome - Sanchez, Phillip; Farkhondeh, Atena; Pavlinov, Ivan; Baumgaertel, Karsten; Rodems, Steven; Zheng, Wei (Frontiers in Pharmacology, 2021)
Advancements in treatment for the rare genetic disorder known as Alagille Syndrome (ALGS) have been regrettably slow. The large variety of mutations to the JAG1 and NOTCH2 genes which lead to ALGS pose a unique challenge for developing targeted treatments. Due to the central role of the Notch signaling pathway in several cancers, traditional treatment modalities which compensate for the loss in activity caused by mutation are rightly excluded. Unfortunately, current treatment plans for ALGS focus on relieving symptoms of the disorder and do not address the underlying causes of disease. Here we review several of the current and potential key technologies and strategies which may yield a significant leap in developing targeted therapies for this disorder.